A concept-based approach for retrieving alternate web services. (18th September 2006) - Peng, Dunlu; Wang, Xiaoling; Zhou, Aoying
Although some standards have been proposed to make web service applicable in recent years, service discovery is still a challenge. Currently, in order to request a specific web service successfully, requestors need to have a complete knowledge of the service provider interface and the profile; however, this is burdensome for general users. On the other hand, once the requested web service is becoming unavailable, the requestors' applications may be unworkable for lack of valid methods to retrieve the alternates of a requested web service. This paper studies the service-discovery problem and presents a concept-based approach to retrieve the optimal alternates for a given web service, which is based on Formal Concept Analysis (FCA) and concept lattice. Compared with other related works, the proposed approach is more efficient and accurate in which the underlying semantics of web services and users' requirements are exploited during the processing of the retrieval.